Moxibustion regulates the polarization of macrophages through the IL-4/STAT6 pathway in rheumatoid arthritis. (April 2022) - Zhong, Yu-mei; Zhang, Lin-lin; Lu, Wen-ting; Shang, Ya-nan; Zhou, Hai-yan
Highlights: The research took IL-4/STAT6 pathway as the entry point to observe the effects of moxibustion on the expression of macrophages and related inflammatory factors in RA rats. The study starts with the polarization of macrophages to explore the anti-inflammatory mechanism of moxibustion. Abstract: Objective: To observe the effects of moxibustion on "Shenshu" and "Zusanli" on macrophage polarization and IL-4/STAT6 signaling pathway in rats with rheumatoid arthritis (RA). To further explore the possible anti-inflammatory mechanism of moxibustion in the treatment of RA. Methods: The rats' right hind paws were injected with freund's complete adjuvant (FCA) to establish the model of RA. Seven days after the injection of FCA, moxibustion therapy was performed on the acupoints of Shenshu (BL23) and Zusanli (ST36) once a day for three weeks. The researchers measured the thickness of the foot pad. ELISA and Histological Analysis were performed to observe the anti-inflammatory effect of moxibustion. Then researchers detected the expression of macrophage phenotype and the expression of IL-4/STAT6 signaling pathway related molecules. Results: It was observed that after the injection of FCA, the rats' feet showed obvious symptoms of redness and swelling. But the symptoms were significantly improved when moxibustion was employed. The study found lower IL-23 and higher IL-4 level in the serum of FCA-injected rats after moxibustion treatment. HE staining showed that the synovium of the RA group was hyperemia and edema, with a large number of inflammatory cells infiltration and vascular dilatation. In the moxibustion group, the degree of synovial hyperemia and edema was improved, and the infiltration of inflammatory cells and vascular dilation were reduced. The study also found that there wer differences among the expressions of macrophage phenotypes in RA, and this was shown by the high expression of CD86 and low expression of CD206. However, the polarization of macrophages in the moxibustion group changed, and that was manifested by enhanced M2-polarized Mφs and inhibited M1-polarized Mφs. Meanwhile, moxibustion suppressed the activation of JAK1, JAK3 and STAT6 in the IL-4/STAT6 signaling pathway, which contributed to the polarization of M2 . Conclusion: The results demonstrate that moxibustion not only suppresses the polarization of M1, but also promotes the polarization of M1. The anti-inflammatory effect of moxibustion may be related to the regulation of macrophage polarization through IL-4/STAT6 signaling pathway.